Analysis of the Quality of Land Transportation Services at the Transportation Agency of Central Maluku Regency, Indonesia - M Parinussa, Ronald; Laurens, Samson; Normawati, Normawati (Jurnal Studi Ilmu Pemerintahan, 2024)
This research seeks to assess and interpret the effectiveness of land transportation services offered by the Transportation Agency of Central Maluku Regency. The qualitative approach relied on gathering data through interviews using a predetermined guide, document tracing, and obtaining other pertinent documents. Secondary data was collected from working papers, legal documents, regional legal documents, brochures, and other legal document analyses pertaining to transportation services. Qualitative analysis techniques were applied to the data. The results indicated that the agency of transportation makes it a point to provide service with five distinct features, which include: serviceability—facilities and infrastructure; reliability—competence and capability; responsiveness—quick and adequate service; assurance—security and guarantees; and empathy—engagement. Central Maluku residents are, therefore, greatly satisfied with the land transportation services offered to them. The public service satisfaction model analysis presented increases in trust and responsibility when the standards are upheld, thus leading to improvements in the region and service effectiveness. The implications of the findings indicate that the agency should focus on improving responsiveness, reliability, and serviceability to maintain satisfaction.